2012
DOI: 10.5402/2012/616759
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression: Is Mode of Delivery a Risk Factor?

Abstract: There are various factors related to postpartum depression. In this study we have aimed to determine the effect of mode of delivery on the risk of postpartum depression. A total of 318 women who applied for delivery were included in the study. Previously diagnosed fetal anomalies, preterm deliveries, stillbirths, and patients with need of intensive care unit were excluded from the study. Data about the patients were obtained during hospital stay. During the postpartum sixth week visit Edinburgh postnatal depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
61
5
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 35 publications
13
61
5
14
Order By: Relevance
“…6 Additional risk factors include lack of social support, stressful life events, and pregnancy complications. 4,6,7 Numerous studies have explored the association between cesarean delivery and postpartum depression, [8][9][10][11][12][13][14][15][16] and most studies have concluded that mode of delivery is not a predictor. [8][9][10][11]13,15 However, a patient's antepartum delivery preferences may play an important role in the determination of how a woman perceives her childbirth experience and outcome, which potentially could affect her risk for postpartum depression.…”
mentioning
confidence: 99%
“…6 Additional risk factors include lack of social support, stressful life events, and pregnancy complications. 4,6,7 Numerous studies have explored the association between cesarean delivery and postpartum depression, [8][9][10][11][12][13][14][15][16] and most studies have concluded that mode of delivery is not a predictor. [8][9][10][11]13,15 However, a patient's antepartum delivery preferences may play an important role in the determination of how a woman perceives her childbirth experience and outcome, which potentially could affect her risk for postpartum depression.…”
mentioning
confidence: 99%
“…Yapılan çalışma sonuçlarına göre, maternal yaşın küçük olması (12)(13)(14)(15) , eşin eğitim seviyesinin düşük olması (4,15) , geniş ailede yaşama (16) , sosyoekonomik durumun kötü olması (4,6,12,14) , istenmeyen gebelik (5,8,(16)(17)(18)(19) , sosyal destek veya eş desteğinin eksik olması (2,8,14,17,19,(20)(21)(22) , psikiyatrik tedavi öyküsünün varlığı (14,15,17,19,21,22) , erken doğum (4) , acil sezaryen olma (13) , doğum sonrası kontraseptif kullanımda eksiklik (23) ve gebeliğinde D vitamini eksikliği yaşama (25,26) durumunun PD için risk faktörü olduğu belirlenmiştir.…”
Section: Bulgularunclassified
“…Literatürde de annenin ileri yaş olması, çalışmıyor olması ve sosyal desteğinin olmaması PD'u etkileyen önemli risk faktörleri olarak bulunmuştur (2,17,(19)(20)(21)(27)(28)(29)(30) . İleri anne yaşı PD için risk faktörü olmasının yanı sıra adolesan anneler de PD için risk altındadır (12,13) .…”
Section: Erzurumunclassified
See 1 more Smart Citation
“…Gebelikte kullanılmış ilaçların ölçülen kontrendikasyon oranları ise %0.9-%4.6 arasındadır. 5 Göker ve ark 6 tarafından yapılan çalışmada 2005-2010 yılları arasında gebelikte en sık kullanılan ilaç grupları antidepresanlar ve antibiyotikler olarak belirlenmiştir. Olukman ve ark 7 tarafından yapılan çalışmada ise ilk sırada antiinfektifler, ardından analjezikler, antidepresanlar ve antigribal ilaçlar yer almıştır.…”
Section: -3unclassified